Analisis Faktor-Faktor Yang Mempengaruhi Keselamatan Penerbangan Pada Bandar Udara Kelas II Lede Kalumbang Tambolaka - Mayada, Erikson; Sulistyowati, Sulistyowati; Retno Mulatsih (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2026)
Based on Law No. 1 of 2009 concerning Aviation, it is explained that aviation is controlled by the State and the Government only conducts coaching. One of the forms of guidance carried out by the government is to improve the ability and role of airports as well as aviation safety and security by ensuring the availability of adequate flight paths and flight navigation in order to support air security. This study aims to determine the influence of Safety management system, safety culture and competence of air traffic guides on flight safety at Lede Kalumpbang airport. The population in this study is Lede Kalumbang airport employees / crew and the sample used in this study is 82 respondents. The data collection methods used were observation (observation), interviews, and questionnaire distribution. The sampling technique used is non-probability sampling type of saturated sampling, then the data is analyzed using multiple linear regression with the help of (software) Statistic Package For Social Science (SPSS) Version 26. The formulation of regression in this study is as follows: Y = 405 + 0.308X1 + 0.197X2 + 0.443X3 + μ. From this equation, it is known that the most dominant variable that affects flight safety is the variable of Guide Competency with a regression coefficient of 0.447. The R2 test (R square) obtained a result of 0.602 or 60.29% which means that the satisfaction of service users is influenced by the variables of safety management system (X1), Safety culture (X2) and guide competence (X3). While the rest (100%-60.2% = 39.8%) is explained by other variables such as traffic supervision, weather, and others.